Ten years of IRCAD, Barretos, SP, Brazil - Crema,Eduardo (2022)
ABSTRACT Minimally invasive surgery represented a significant milestone in modern surgery; however, continuous innovation and the emergence of new technologies pose new challenges in terms of surgical learning curves since new interventions are associated with increased surgical complexity and a higher risk of complications. For this reason, surgeons are aware of the beneficial effects of “learning before doing” and the importance of safely implementing new surgical procedures in order to obtain better patient outcomes. Considered the largest Latin American training center in minimally invasive surgery, IRCAD Barretos, São Paulo, Brazil, makes it possible to acquire surgical skills through training in different and the most complex areas of medicine, providing the experience of real and simulated situations, with focus on innovation. The center possesses state-of-the-art infrastructure and technology, with a very high-level teaching staff and an affectionate and hospitable reception. Since its inauguration, in 2011, the center has already qualified numerous professionals and has placed the country in a privileged position in terms of surgical knowledge. The present article describes the activities developed over these ten years of the institute in Brazil as the largest training center for surgeons of the continent in order to address the importance of surgical skills training.